2013
DOI: 10.1155/2013/697051
|View full text |Cite
|
Sign up to set email alerts
|

In SilicoScreening and Molecular Dynamics Simulation of Disease-Associated nsSNP in TYRP1 Gene and Its Structural Consequences in OCA3

Abstract: Oculocutaneous albinism type III (OCA3), caused by mutations of TYRP1 gene, is an autosomal recessive disorder characterized by reduced biosynthesis of melanin pigment in the hair, skin, and eyes. The TYRP1 gene encodes a protein called tyrosinase-related protein-1 (Tyrp1). Tyrp1 is involved in maintaining the stability of tyrosinase protein and modulating its catalytic activity in eumelanin synthesis. Tyrp1 is also involved in maintenance of melanosome structure and affects melanocyte proliferation and cell d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 65 publications
2
57
0
Order By: Relevance
“…The structural analyses of native and mutant Tyrp1 proteins were scrutinized by molecular modelling and molecular dynamics simulation (MDS) approach. From this analysis we confirmed that, TYRP1 protein alter the structural conformation and loss the flexibility behaviour upon mutation [75]. The structural alteration of TYRP1 protein upon mutation was clearly discussed and shown in our previous studies (Figure 4) [75].…”
Section: Computational Screening Of Pathological Mutation and Theisupporting
confidence: 83%
“…The structural analyses of native and mutant Tyrp1 proteins were scrutinized by molecular modelling and molecular dynamics simulation (MDS) approach. From this analysis we confirmed that, TYRP1 protein alter the structural conformation and loss the flexibility behaviour upon mutation [75]. The structural alteration of TYRP1 protein upon mutation was clearly discussed and shown in our previous studies (Figure 4) [75].…”
Section: Computational Screening Of Pathological Mutation and Theisupporting
confidence: 83%
“…Molecular simulation analysis revealed the SNPs influence over the proteins playing a role in the defense response (PR1) and metabolic activities; both are noteworthy phenotypic difference known to exist in both the species. A similar approach was applied in earlier studies434445 to study the influence of non-synonymous SNPs. Present study must enhance the knowledge of the scientific community and provide support for the future breeding program.…”
Section: Discussionmentioning
confidence: 99%
“…The organized platform for the analysis and estimations of pathological consequence of genetic mutations and in determining their basic molecular mechanism [8][9][10][11][12][13]. In this study, we have tried to find out most deleterious and disease associated nsSNPs in coding region of STEAP2 out of dataset obtained from ENSEMBL by using computational tools and then checked their effects on structure of protein [13,14].…”
Section: Polyphen2mentioning
confidence: 99%
“…PolyPhen2 calculates the probability for a given mutation to be benign, possibly damaging or probably damaging. If score is nearer to 1, nsSNPs will probably be damaging [11,19].…”
Section: Refinement Of Protein Modelmentioning
confidence: 99%